SCIENCE AND TECHNOLOGY IN ISLAM AS A MEANS OF HUMAN WELL-BEING AND DEVOTION TO ALLAH - Sholihat, Khodijah Amatulloh; Jamroji, Bagus; Waahsturi; Handoko; Irawan, Wahyudi Saputra (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The development of science and technology in modern life has significantly influenced human quality of life. However, without moral and spiritual foundations, such progress may generate ethical and humanitarian challenges. Islam views science and technology not merely as instruments for mastering nature, but also as a trust (amanah) and a means of drawing closer to Allah Subhanahu wa Ta‘ala. This study aims to examine the Islamic perspective on science and technology, analyze the concept of maslahah as an orientation for their development, and explain how science and technology can function as forms of devotion to Allah. This research employs a qualitative approach using a literature review method, drawing on primary Islamic sources and relevant scholarly works. The findings indicate that Islam emphasizes a balanced integration of rational, ethical, and spiritual dimensions in the development of science and technology. The principle of maslahah, aligned with the maqāṣid al-sharī‘ah, serves as a key ethical framework to ensure that scientific and technological advancement contributes to human well-being, social justice, and spiritual responsibility